الطاقة الشمسية كبديل مستدام - التجربة المصرية - مهاوات, لعبيدي; جرموني, أسماء (جامعة الوادي - University of Eloued, 2018)
تهدف هذه الورقة البحثية إلى تسليط الضوء على موضوع الطاقة المتجددة وخاصة منها الطاقة الشمسية والتي تشكل أحد الأساليب الحديثة في إنتاج الطاقة، باعتبارها طاقة نظيفة وبديلة للطاقة الأحفورية التي تتسبب في الإنبعاثات الكربونية والتلوث البيئي وإحداث التغييرات المناخية، وذلك في سبيل الحفاظ على البيئة من ناحية، وإيجاد مصادر وأشكال أخرى من الطاقة تكون لها إمكانية الاستمرارية والتجدد من ناحية أخرى، وقد تم التطرق إلى التجربة المصرية في هذا المجال باعتبارها إحدى الدول التي تزخر بالطاقة الشمسية ولها شراكات وأبحاث أوروبية The aim of this paper is to highlight the theme of renewable energy, which constitute one of the modern methods of production of energy, as a clean energy alternative to fossil energy that cause carbon emissions and environmental pollution and causing climatic changes, and in order to preserve on the one hand, and finding sources and other forms of energy shall have the environment to identify the most important types of possibility of continuity and renewal on the other hand, It was addressed to the Egyptian experience in this area as one of the countries that is rich in solar energy and its European partnerships and research.
Solar Energy as a Sustainable Alternative - The Egyptian Experience
مقال
Keywords: الطاقة المتجددة، الطاقة الشمسية، التجربة المصرية.; Renewable energy; solar energy; the Egyptian experience.